A Retrospective Study of Latissimus Dorsi Flap in Immediate Breast Reconstruction - Zheng, Hongmei; Zhu, Guodong; Guan, Qing; Fan, Wei; Li, Xiang; Yu, Mancheng; Xu, Juan; Wu, Xinhong (Frontiers in Oncology, 2021)
Background There are many different methods used for immediate breast reconstruction, but the advantages and disadvantages between distinct methods are not reported and compared directly. Methods We collected the patient data who underwent breast reconstruction from 2010 to 2015 and classified the total 103 patients into three groups: (ⅰ) Skin- or nipple-sparing mastectomy with implant and partial latissimus dorsi flap (MIPLD); (ⅱ) Skin- or nipple-sparing mastectomy with the whole latissimus dorsi flap (MWLD); and (ⅲ) Breast conservative surgery with partial latissimus dorsi flap (BCSPLD). The outcome, safety, and cosmetic outcome of the latissimus dorsi muscle flap with or without implant were reported and compared. Results The procedures were successful in all cases. None of the patients had severe complications. The 5-year distant metastasis-free survival is 94.2%. All the patients exhibited good arm and back function. Based on the evaluation of the BREAST-Q score, the cosmetic outcome of Satisfaction with Breasts was excellent or good in 97.8% of the cases. Conclusions MIPLD, MWLD, and BCSPLD stand for three distinct methods for immediate breast reconstruction with good outcome and aesthetic effect. They were safe, easy to perform, and provided quick recovery and good quality of life. Therefore, these three breast reconstructive methods are worthy of widespread use in clinical practice, and provide different ways to reconstruct the breast according to the patients’ conditions and preferences.